CLINIC-STATISTYC ANALYSIS ABOUT CHRONIC OBSTRUCTIVE PULMONARY DISEASES IN INANO-FRANKIVSK REGION - Малофій, Л. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
We analyzed the incidence of chronic obstructive pulmonary diseases in Ivano-Frankivsk region during the period from 1990 till 2009 (20 years) according to dictates of regional pulmonological center in Ivano-Frankivsk and studied data of primary disability of patients with COPD according to the pulmonological Medical and Social Expert Commission during 1994 -2009. We analyzed index of mortality caused by chronic obstructive lung diseases according to data of pathologoanatomic centralized department of regional hospital in Ivano-Frankivsk during 50 years (from 1960 till 2009). It was found that the incidence among the adult population since 1990 gradually and smoothly increased till 2003 from 20,775.8 to 29,654.1 per 100 thousand people, when it reached the peak, and then until 2008 a small decline was observed (26904.8 per 100 thousand people). Mortality dynamics because of COPD during 50 years in Ivano-Frankivsk region had a constant tendency to increase with periodic ups and downs. It was found that the total number of autopsies of deceased due to COPD during the explored period constitutes 16,8% of total number of autopsies. Among the dead men (62%). 49% of the deceased were of working age.